2019
DOI: 10.1002/ijc.32032
|View full text |Cite
|
Sign up to set email alerts
|

Hot beverages and oesophageal cancer risk in western Kenya: Findings from the ESCCAPE case–control study

Abstract: Oesophageal squamous cell carcinoma (ESCC) has markedly high incidence rates in Kenya and much of East Africa, with a dire prognosis and poorly understood aetiology. Consumption of hot beverages—a probable carcinogen to humans—is associated with increased ESCC risk in other settings and is habitually practiced in Kenya. We conducted a case–control study in Eldoret, western Kenya between August 2013 and March 2018. Cases were patients with endoscopically confirmed oesophageal cancer whose histology did not rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 15 publications
4
29
1
Order By: Relevance
“…However, the evidence base for ESCC in Africa is relatively thin and not entirely consistent 2 . Since then, alcohol and hot beverages have been identified as risk factors in Kenya 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence base for ESCC in Africa is relatively thin and not entirely consistent 2 . Since then, alcohol and hot beverages have been identified as risk factors in Kenya 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for developing ESCC include tobacco consumption (smoking)[3-5], heavy alcohol consumption[6,7], drinking hot tea[8,9], consuming red meat[10], poor oral health[11], low intake of fresh fruit and vegetables[10,12], and low socioeconomic status[6,13]. Esophageal mucosa dysplasia from acid reflux and Barrett’s esophagus is a risk factor for developing EAC[14].…”
Section: Introductionmentioning
confidence: 99%
“…Our institution is undertaking a case-control trial on the risk factors for ESCC, the validation and information of the questionnaire will help in the understanding of hot chai as a risk factor. A case-control study from Eldoret in Kenya reported an association between hot beverages and ESCC 24 . Although no temperature measurements were included, the controls reported consuming “very hot”, “hot”, and “warm” tea in 7%, 68%, and 25%, respectively, which is quite similar to our distribution of 11%, 64%, and 25%.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study from Tanzania has measured beverage temperature, and it found that the participants drank their beverages (mainly tea) at an average temperature of 70.6 °C, higher than that reported in previous studies from other populations 23 . A recent case-control study by Middleton et al in Kenya, showed an association between self-reported ingestion of hot beverages with ESCC 24 . Historically, studies have utilized participant self-assessed questionnaires to report on their preferences for the temperature.…”
Section: Introductionmentioning
confidence: 96%